(untitled) (LEARNing Landscapes, 2017)
Education changes the brain. The purpose of this meta-review is to afford teachers access to the most upto- date research regarding principal neuro-processes of adolescent development and behavior to improve students’ well-being and motivation in the classroom. This includes facets such as emotional, social, risk and reward mechanisms, stressors, technology, and learning. Understanding the scientific basis behind processes, such as learning and memory, empowers teachers with the knowledge to quantify the effects of their teaching on the brain, to facilitate successful learning, and to contribute to the present as well as future health and well-being of their adolescent students.